Determination of carcinogenic herbicides in milk samples using green non-ionic silicone surfactant of cloud point extraction and spectrophotometry - Mohd, Noraini; Zain, Nur Nadhirah Mohamad; Raoov, Muggundha; Mohamad, Sharifah (The Royal Society, 2018)
A new cloud point methodology was successfully used for the extraction of carcinogenic pesticides in milk samples as a prior step to their determination by spectrophotometry. In this work, non-ionic silicone surfactant, also known as 3-(3-hydroxypropyl-heptatrimethylxyloxane), was chosen as a green extraction solvent because of its structure and properties. The effect of different parameters, such as the type of surfactant, concentration and volume of surfactant, pH, salt, temperature, incubation time and water content on the cloud point extraction of carcinogenic pesticides such as atrazine and propazine, was studied in detail and a set of optimum conditions was established. A good correlation coefficient (R2) in the range of 0.991–0.997 for all calibration curves was obtained. The limit of detection was 1.06 µg l−1 (atrazine) and 1.22 µg l−1 (propazine), and the limit of quantitation was 3.54 µg l−1 (atrazine) and 4.07 µg l−1 (propazine). Satisfactory recoveries in the range of 81–108% were determined in milk samples at 5 and 1000 µg l−1, respectively, with low relative standard deviation, n = 3 of 0.301–7.45% in milk matrices. The proposed method is very convenient, rapid, cost-effective and environmentally friendly for food analysis.